Regionally endothermic traits in planktivorous basking sharks Cetorhinus maximus - Dolton, Haley R.; Jackson, Andrew L.; Deaville, Robert; Hall, Jackie; McManus, Gavin; Perkins, Matthew W.; Rolfe, Rebecca A.; Snelling, Edward P.; Houghton, Jonathan D.R.; Sims, David W.; Payne, Nicholas L. (Endangered Species Research, 2023)
Few fast-swimming apex fishes are classified as ‘regional endotherms’, having evolved a relatively uncommon suite of traits (e.g. elevated body temperatures, centralised red muscle, and thick-walled hearts) thought to facilitate a fast, predatory lifestyle. Unlike those apex predators, Endangered basking sharks Cetorhinus maximus are massive filter-feeding planktivores assumed to have the anatomy and physiology typical of fully ectothermic fishes. We combined dissections of stranded specimens with biologging of free-swimming individuals and found that basking sharks have red muscle located medially at the trunk, almost 50% compact myo - cardium of the ventricle, and subcutaneous white muscle temperatures consistently 1.0 to 1.5°C above ambient. Collectively, our findings suggest basking sharks are not full ectotherms, instead sharing several traits used to define a regional endotherm, thus deviating from our current understanding of the species and questioning the link between physiology and ecology of regionally endothermic shark species. With successful forecasting of population dynamics and distribution shifts often improved by accurate physiological data, our results may help explain movement patterns of the species, which could ultimately facilitate conservation efforts. http://www.int-res.com/journals/esr/esr-home/ Anatomy and Physiology SDG-14:Life below water